PENGARUH BUDAYA ORGANISASI, GAYA KEPEMIMPINAN TRANSFORMASIONAL, KETERAMPILAN KOMUNIKASI, DAN BEBAN KERJA TERHADAP LOYALITAS KARYAWAN RUMAH SAKIT SWASTA DI SURABAYA - Yuliana, Yuliana; Jayanagara, Oscar (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
Examining and analyzing how working culture, transformational leadership, communication skills, and workload affect employee loyalty is the purpose of this study. The methodology used in this research is survey method with cross-section data collection through questionnaires shared to respondents by using the Google Form platform. The sample was obtained by convenience sampling as many as 39 peoples who worked at private hospitals in Surabaya City area. Structural Equation Modeling is a data analysis technique used in hypothesis testing (SEM).The research results provide evidence organizational culture, transformational leadership style, communication skills and workload have a positive effect and significant on employee loyalty who worked at private hospitals in Surabaya city.